Novel Method of Cell-Free In Vitro Synthesis of the Human Fibroblast Growth Factor 1 Gene - Zuo, Peijun (Hindawi Publishing Corporation, 2010)
Recombinant DNA projects generally involve cell-based gene cloning. However, because template DNA is not always readily available, in vitro chemical synthesis of complete genes from DNA oligonucleotides is becoming the preferred method for cloning. This article describes a new, rapid procedure based on Taq polymerase for the precise assembly of DNA oligonucleotides to yield the complete human fibroblast growth factor 1 (FGF1) gene, which is 468 bp long and has a G+C content of 51.5%. The new method involved two steps: (1) the design of the DNA oligonucleotides to be assembled and (2) the assembly of multiple oligonucleotides by PCR to generate the whole FGF1 gene. The procedure lasted a total of only 2 days, compared with 2 weeks for the conventional procedure. This method of gene synthesis is expected to facilitate various kinds of complex genetic engineering projects that require rapid gene amplification, such as cell-free whole-DNA library construction, as well as the construction of new genes or genes that contain any mutation, restriction site, or DNA tag.